INVESTMENTS AND INNOVATIONS IN THE OPERATING ACTIVITIES OF AGRICULTURAL ENTERPRISES IN THE CONDITIONS OF THE CRISIS OF THE MARTIAL STATE - SAKUN, Lesia; MAZHARENKO, Kateryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the issue of the impact of investments and innovations on the operational management system of the agro-industrial complex enterprises, where the prospects of the industry and the main aspects of activity in crisis conditions during martial law are outlined. The relevance of the topic has been determined, the essence of the concepts «investment», «innovations», «operational activity», «crisis» and have been analyzed. The key directions of investments and their implementation in the leading agricultural holdings of Ukraine (according to the index of innovativeness of the mind) have been studied. It has been found that the use of software solutions for budget management can significantly simplify data processing and minimize the impact of the human factor. Such programs also allow monitoring of indicators in real time due to constant updates. Robotic solutions for operational activity agribusiness have been analyzed, in particular, the use of devices that can perform routine tasks in the field and measure soil parameters, its humidity, etc. The essence of the work of agricultural spraying drones from the DroneUA company has been considered, the advantages and prospects of their use have been determined. This approach is aimed at making the transition from an extensive to a more progressive innovation-investment model of development. An analysis of capital investments in various sectors of economic activity, including costs, also has been conducted. It has been found that despite the significant losses suffered by the agricultural sector in the crisis conditions during the war, most of the leading agricultural companies in Ukraine managed to withstand this test and maintain their positions thanks to crisis management tools, effective cooperation and assistance from partners.